2000
DOI: 10.1001/archpedi.154.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hemorrhage in an Infant Following 2 Weeks of Fungal Exposure

Abstract: Avoidance of unnecessary exposure of infants to fungus growth in water-damaged environments or exposure to tobacco smoke is prudent. Further investigation into the toxic effects of indoor fungi as causes of infantile pulmonary hemorrhage is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…As the conidia of T. harzianum are produced in slimy masses on conidiophores, the percentage of release or dispersal of conidia from the growing substratum is very low, up to 0.03% of its conidia, when exposed to airflow ). This phenomenon might explain the inconsistent seasonal occurrence of T. harzianum as found in this as well as in earlier studies (Horner et al 2004;Domsch et al 1993;Novotny and Dixit 2000).…”
Section: Discussionsupporting
confidence: 76%
“…As the conidia of T. harzianum are produced in slimy masses on conidiophores, the percentage of release or dispersal of conidia from the growing substratum is very low, up to 0.03% of its conidia, when exposed to airflow ). This phenomenon might explain the inconsistent seasonal occurrence of T. harzianum as found in this as well as in earlier studies (Horner et al 2004;Domsch et al 1993;Novotny and Dixit 2000).…”
Section: Discussionsupporting
confidence: 76%
“…At the beginning of the 18th century, Ramazzini, considered "the father of occupational medicine," described an illness of workers inhaling 'foul and mischievous powder' from handling crops (116,302). More recently, Platt et al (333), found that occupants of wet, moldy buildings had an increase in subjective complaints.…”
Section: Indoor Air and Building-related Illnessmentioning
confidence: 99%
“…While they found mycotoxins (including riordin L-2, roridin E, and satratoxin H) in contaminated wallboard, they did not assay for other compounds. In another case of pulmonary hemorrhage related to fungal exposure, the infant was formula fed and exposed to tobacco smoke (302). Again, there were a host of laboratory abnormalities, particularly renal.…”
Section: Effects Of Stachybotrys In Indoor Air 155mentioning
confidence: 99%
See 1 more Smart Citation
“…Stachybotrys was implicated as a causative agent of pulmonary hemorrhage in several case reports [40][41][42] and in more than 30 infants in the Cleveland area during the 1990s. In Cleveland, a case-control study determined that the affected infants were more likely than control infants to have lived in water-damaged homes in which Stachybotrys was isolated [43].…”
Section: Stachybotryotoxicosismentioning
confidence: 99%